Inhibition of Epithelial-Mesenchymal Transition and Metastasis by Combined TGFbeta Knockdown and Metformin Treatment in a Canine Mammary Cancer Xenograft Model - Leonel, Camila [UNESP]; Borin, Thaiz Ferraz; de Carvalho Ferreira, Lï¿½via [UNESP]; Moschetta, Marina Gobbe; Bajgelman, Marcio Chaim; Viloria-Petit, Alicia M.; de Campos Zuccari, Debora Aparecida Pires [UNESP] (My University, 2017)
Epithelial mesenchymal transition (EMT) is a process by which epithelial cells acquire mesenchymal properties, generating metastases. Transforming growth factor beta (TGF-β) is associated with this malignancy by having the ability to induce EMT. Metformin, has been shown to inhibit EMT in breast cancer cells. Based on this evidence we hypothesize that treatment with metformin and the silencing of TGF-β, inhibits the EMT in cancer cells. Canine metastatic mammary tumor cell line CF41 was stably transduced with a shRNA-lentivirus, reducing expression level of TGF-β1. This was combined with metformin treatment, to look at effects on cell migration and the expression of EMT markers. For in vivo study, unmodified or TGF-β1sh cells were injected in the inguinal region of nude athymic female mice followed by metformin treatment. The mice’s lungs were collected and metastatic nodules were subsequently assessed for EMT markers expression. The migration rate was lower in TGF-β1sh cells and when combined with metformin treatment. Metformin treatment reduced N-cadherin and increased E-cadherin expression in both CF41 and TGF-β1sh cells. Was demonstrated that metformin treatment reduced the number of lung metastases in animals bearing TGF-β1sh tumors. This paralleled a decreased N-cadherin and vimentin expression, and increased E-cadherin and claudin-7 expression in lung metastases. This study confirms the benefits of TGF-β1 silencing in addition to metformin as potential therapeutic agents for breast cancer patients, by blocking EMT process. To the best of our knowledge, we are the first to report metformin treatment in cells with TGF-β1 silencing and their effect on EMT.
Keywords: Anticarcinogenic agents; Breast cancer; Metastasis; shRNA; TGF-β